Longitudinal study on enterovirus A71 and coxsackievirus A16 genotype/subgenotype replacements in hand, foot and mouth disease patients in Thailand, 2000–2017. (March 2019) - Noisumdaeng, Pirom; Korkusol, Achareeya; Prasertsopon, Jarunee; Sangsiriwut, Kantima; Chokephaibulkit, Kulkanya; Mungaomklang, Anek; Thitithanyanont, Arunee; Buathong, Rome; Guntapong, Ratigorn; Puthavathana, Pilaipan
Highlights: This longitudinal study explored the enterovirus A71 (EV-A71) and coxsackievirus A16 (CV-A16) subgenotypic replacements. Emerging EV-A71 subgenotypes and the duration of circulation was revealed over time. EV-A71 and CV-A16 are the dominant viruses associated with hand, foot and mouth disease in Thailand. Abstract: Background: Enterovirus A71 (EV-A71) and coxsackievirus A16 (CV-A16) are the major causative agents of hand, foot and mouth disease (HFMD) worldwide, particularly in the Asia-Pacific region. Several strains have emerged, circulated, and faded out over time in recent decades. This study investigated the EV-A71 and CV-A16 circulating strains and replacement of genotypes/subgenotypes in Thailand during the years 2000–2017. Methods: The complete VP1 regions of 92 enteroviruses obtained from 90 HFMD patients, one asymptomatic adult contact case, and one encephalitic case were sequenced and investigated for serotypes, genotypes, and subgenotypes using a phylogenetic analysis. Results: The 92 enterovirus isolates were identified as 67 (72.8%) EV-A71 strains comprising subgenotypes B4, B5, C1, C2, C4a, C4b and C5, and 25 (27.2%) CV-A16 strains comprising subgenotypes B1a and B1b. Genotypic/subgenotypic replacements were evidenced during the study period. EV-A71 B5 and C4a have been the major circulating strains in Thailand for more than a decade, and CV-A16 B1a has been circulating for almost two decades. Conclusions: This study provides chronological data on the molecular epidemiology of EV-A71 and CV-A16 subgenotypes in Thailand. Subgenotypic replacement frequently occurred with EV-A71, but not CV-A16. Monitoring for viral genetic and subgenotypic changes is important for molecular diagnosis, vaccine selection, and vaccine development.